The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/nu13020562
|View full text |Cite
|
Sign up to set email alerts
|

Low Zinc Levels at Admission Associates with Poor Clinical Outcomes in SARS-CoV-2 Infection

Abstract: Background: Zinc is an essential micronutrient that impacts host–pathogen interplay at infection. Zinc balances immune responses, and also has a proven direct antiviral action against some viruses. Importantly, zinc deficiency (ZD) is a common condition in elderly and individuals with chronic diseases, two groups with an increased risk for severe severe coronavirus disease 2019 (COVID-19) outcomes. We hypothesize that serum zinc content (SZC) influences COVID-19 disease progression, and thus might represent a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 33 publications
3
54
1
7
Order By: Relevance
“…In the present study, apart from insufficient vitamin D intake, it was also identified that the assessed patients positive for SARS-CoV-2 had insufficient intakes of vitamin E, calcium, iron, and zinc, based on the RDA’s for the Mexican population. According to a study reported by Vogel-Gonzalez, et al [ 49 ], COVID-19 patients with a serum zinc concentration <50 μg/dL presented a higher inflammatory state and greater clinical severity of the disease. In regard to zinc status, in vitro studies have reported that zinc ions play a role in the antiviral immune response by inducing the production of interferons (IFN-α and IFN-γ) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, apart from insufficient vitamin D intake, it was also identified that the assessed patients positive for SARS-CoV-2 had insufficient intakes of vitamin E, calcium, iron, and zinc, based on the RDA’s for the Mexican population. According to a study reported by Vogel-Gonzalez, et al [ 49 ], COVID-19 patients with a serum zinc concentration <50 μg/dL presented a higher inflammatory state and greater clinical severity of the disease. In regard to zinc status, in vitro studies have reported that zinc ions play a role in the antiviral immune response by inducing the production of interferons (IFN-α and IFN-γ) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral property of zinc has been studied extensively, including coronavirus, hepatitis C virus, and HIV infections [70,71]. Pre-existing zinc deficiency may pre-dispose patients to a severe progression of COVID-19 [72,73]. Zinc supplementation may reduce the incidence of acute lower respiratory infection [74].…”
Section: Zincmentioning
confidence: 99%
“…A number of association and intervention studies have investigated the role of zinc in COVID-19 infection [71,73,76,77]. In a small study of COVID-19 patients, 27 of 45 (57.4%) were found to be zinc deficient, and these patients exhibited higher rates of complications compared to zinc sufficient patients, including higher rates of acute respiratory distress syndrome (18.5% vs 0%, p ¼ 0.06), corticosteroid therapy (p ¼ 0.02), prolonged hospital stay, and increased mortality (18.5% vs 0%, p ¼ 0.06).…”
Section: Zincmentioning
confidence: 99%
“…Major damages caused by Zn deficiency are growth failure, hair loss, dermatitis, diarrhoea, appetite loss, and neurosensory, skeletal, reproductive, and immune system disorders (Roohani et al 2013 ). In a recent report, Zn was found to be important for balancing immune responses against diseases such as COVID-19, as Zn deficiency is often observed in elderly individuals and individuals with chronic diseases (Vogel-González et al 2021 ). Hence, the consistent intake of Zn through daily cereal consumption may be one of the most efficient ways to mitigate Zn deficiency.…”
Section: Introductionmentioning
confidence: 99%